2006
DOI: 10.1002/jcb.20776
|View full text |Cite
|
Sign up to set email alerts
|

Decorin regulates assembly of collagen fibrils and acquisition of biomechanical properties during tendon development

Abstract: Tendon function involves the development of an organized hierarchy of collagen fibrils. Small leucine-rich proteoglycans have been implicated in the regulation of fibrillogenesis and decorin is the prototypic member of this family. Decorin-deficient mice demonstrate altered fibril structure and mechanical function in mature skin and tail tendons. However, the developmental role(s) of decorin needs to be elucidated. To define these role(s) during tendon development, tendons (flexor digitorum longus) were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
346
4
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 383 publications
(377 citation statements)
references
References 41 publications
23
346
4
4
Order By: Relevance
“…Thus, it was believed that absence of decorin would lead to weaker tissues and that the opposite trend could be expected if decorin is overexpressed. However, either superior or similar material parameters have recently been reported for tendons from decorin deficient adult [37] and postnatal mice [34] as well as decorin deficient engineered gels [16], compared to wild-type controls. In addition, greater than normal decorin expression has been reported in prolapsed mitral valve [38] in which the tissue is weakened [39], and our lab has histochemically demonstrated that excess decorin is present valves that were exposed to altered shear stress [40].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Thus, it was believed that absence of decorin would lead to weaker tissues and that the opposite trend could be expected if decorin is overexpressed. However, either superior or similar material parameters have recently been reported for tendons from decorin deficient adult [37] and postnatal mice [34] as well as decorin deficient engineered gels [16], compared to wild-type controls. In addition, greater than normal decorin expression has been reported in prolapsed mitral valve [38] in which the tissue is weakened [39], and our lab has histochemically demonstrated that excess decorin is present valves that were exposed to altered shear stress [40].…”
Section: Discussionmentioning
confidence: 74%
“…Even though decorin and biglycan are often found in different regions of the extracellular matrix and respond differently to growth factors [4], biglycan competes with decorin for the same binding site on type I collagen fibrils [4]. Thus, compensatory behavior of biglycan has been reported in Dcn −/− cell-seeded collagen gels and native tissues [16,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Together, the PG changes in this overstrained tensile tendon may negatively impact the structural integrity and mechanical properties of the tendon and potentially predispose to rupture. Reduced levels of small leucine-rich PGs would be expected to affect collagen fibrillogenesis and fibril mechanical properties as well as increase the susceptibility of the collagen fibers to cleavage by collagenolytic MMPs (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Although the nature of such interactions in normal cartilage is not well established, collagen-binding molecules (such as type IX collagen and decorin) can regulate collagen fibril length and diameter during development (41,42) and may also mediate the adherence and sliding between collagen fibrils and act as functional noncovalent linkages within the extracellular matrix (43,44). While aggrecan contains most of the chondroitinase ABC-susceptible material of the tissue, depletion of GAG with chondroitinase ABC may alter or displace some of these other chondroitin sulfate-or dermatan sulfate-containing molecules and allow new interactions between collagen fibrils that enhance the tensile integrity of the collagen network.…”
Section: Discussionmentioning
confidence: 99%